CRITICAL DISCOURSE ANALYSIS ON STUDENT PARTICIPATION IN BILINGUAL MATHEMATICS LEARNING - Endah Nur Tjendani; Prima Cristi Crismono; Beby Dwi Febriyanti; Mely Agustin Reni Pitasari; Fitriyatul Hanifiyah (IJIET (International Journal of Indonesian Education and Teaching), 2025)
This research applied Critical Discourse Analysis to investigate how students engage in bilingual mathematics classes at two Islamic boarding schools (pesantrens) in Jember. It aimed to understand how language is used by both students and teachers throughout the learning process and the ways it impacts student involvement. Data were gathered through classroom observations, audio recordings, and field notes. The Initiation-Response-Follow-up (IRF) model was used for analysis. The study revealed that students' ability to participate is closely tied to their confidence in speaking English and the encouragement they receive from teachers. These insights underscored the need for inclusive communication methods and psychological support to boost participation in bilingual classrooms. The research also offered a deeper look at how language functions in educational settings and what that meant for teaching practices in bilingual environments. Ultimately, the findings can help shape more effective teaching strategies within bilingual education, particularly in pesantrens, leading to improved learning experiences and greater student engagement.